Developing research competence through a student-run peer-review journal at higher education institutions of Kazakhstan - Montgomery, D. P.; CohenMiller, A. S.; Kozhabayeva, K. R.; Orynbassarova, D. M. (KAZGUU University. Nazarbayev University. The 2ndInternational Research Conferenceon Academic Integrityis a peerreviewed conference., 2017)
This paper seeks to better understand the general institutional characteristics and the specific participatory activities that help students in higher education develop research competence. This paper presents the first part of an ongoing mixed methods study which uses a quantitative survey of authors (N=30), peer reviewers (N=35) and editors (N=10), followed by qualitative interviews (N=9) of selected representatives from each role, in order to identify and evaluate the ways in which participation in a student-run peer-reviewed journal contributed to developing research competence. In this part, we discuss the state of scholarly research in Kazakhstan, and provide a definition of research competence, and present the methodology employed in this study. The second part of the study will identify strengths of the student-run project, opportunities for improvement, and considerations for application in similar contexts to improve research competence. In this way, it makes a concrete step toward understanding how to improve scholarly research in Kazakhstan.
Keywords: research competence; higher education; student publication; organizational socialization; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education